Coconut Tissue Culture: The Indian Initiatives, Experiences and Achievements - Karun, Anitha; Rajesh, M. K.; Sajini, K. K.; Muralikrishna, K. S.; Neema, M.; Shareefa, M.; Thomas, R. J. (International Coconut Community, 2017)
Coconut is one of the principal crops of India cultivated in over 35 districts mainly in the southern states. The productivity of the crop is declining in many of the traditionally cultivated regions owing to ageing plantations as well as biotic and abiotic stresses. These plantations are to be replanted with high yielding varieties/hybrids for which adequate quantity of quality planting material is not available. Even though tissue culture research was initiated in many laboratories in the country, the work was eventually phased out in most of the laboratories for want of a repeatable protocol. At ICAR-CPCRI, coconut tissue culture programs have been continuing for the past three decades. The attempts made include experimentation with different explants viz., immature inflorescence, plumular tissues, mature palm shoot meristem, ovary and anthers and different culture media supplemented with varying levels and types of hormones. Some of the successful protocols developed at the Institute include coconut zygotic embryo culture for collection and exchange of germplasm, cryopreservation and retrieval of zygotic embryos and pollen and plantlet regeneration from plumular tissues. Even though ICAR-CPCRI has succeeded in obtaining plantlets via direct organogenesis from inflorescence explants, the absence of friable calli formation from explants, the low rate of somatic embryo formation, large number of cultures turning to abnormal shoot development, non conversion of somatic embryos into plantlets, and formation of abnormal somatic embryos remain the major bottlenecks. Gene expression studies are being currently undertaken to decipher the molecular basis of in vitro recalcitrance.